AI-2 Signaling: A Potential Driver of Bacteremia in Non-Typhoidal Salmonella Infections - Li Y; Lu B; Qiang X; Lin Y; He J; Cai Y (Infection and Drug Resistance)
Yu Li,1,2,* Bing Lu,1,3,* Xinhua Qiang,3 Yibin Lin,1 Jie He,2 Yunxiang Cai3 1School of Medicine, Huzhou University, Huzhou, Zhejiang, 313000, People’s Republic of China; 2Department of Infectious Diseases, First Affiliated Hospital of Huzhou University, Huzhou, Zhejiang, 313000, People’s Republic of China; 3Department of Clinical Laboratory, First Affiliated Hospital of Huzhou University, Huzhou, Zhejiang, 313000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jie He, Department of Infectious Diseases, First Affiliated Hospital of Huzhou University, No. 158 Back Square Road, Wuxing District, Huzhou, Zhejiang, 313000, People’s Republic of China, Email hejie@zjhu.edu.cn Yunxiang Cai, Department of Clinical Laboratory, First Affiliated Hospital of Huzhou University, No. 158 Back Square Road, Wuxing District, Huzhou, Zhejiang, 313000, People’s Republic of China, Email caiyunxiang@zjhu.edu.cnIntroduction: Non-typhoidal Salmonella (NTS) infections typically present as localized inflammation near the intestinal mucosal epithelium. However, some NTS strains can breach the intestinal barrier and enter the bloodstream, leading to bacteremia and severe systemic infections. The mechanisms by which NTS invades the bloodstream remain unclear.Methods: In this study, we isolated 36 NTS strains from patients with diarrhea and bacteremia at First Affiliated Hospital of Huzhou University. Strains represented two distinct clinical manifestations, and were subjected to whole-genome sequencing, comparative genomics, and genetic differentiation analysis to identify genes potentially involved in bloodstream invasion. Additionally, we conducted inhibition assays using quercetin, a chemical inhibitor of the identified gene pathways, to validate our findings.Results: Our analysis revealed that genes distinguishing the bloodstream Salmonella isolates from the fecal Salmonella isolates were primarily involved in the AI-2 quorum sensing pathway and biofilm-associated protein transport. Subsequent biofilm formation assays demonstrated that the bloodstream isolates exhibited significantly higher biofilm formation capacity compared to the fecal isolates. Upon the addition of quercetin, biofilm formation was equally inhibited in both groups. Collectively, these findings suggest that genes involved in the AI-2 pathway and biofilm-associated protein transport may be key factors contributing to the development of bacteremia in NTS infections.Keywords: invasive non-typhoidal Salmonella, whole genome sequencing, comparative genomics analysis, biofilm, quorum sensing, AI-2